2022
DOI: 10.1111/acel.13586
|View full text |Cite
|
Sign up to set email alerts
|

DO‐SRS imaging of diet regulated metabolic activities in Drosophila during aging processes

Abstract: Lipid metabolism plays crucial roles during aging processes, but how it is regulated by diets and how it interplays with aging still remain unclear. We proposed a new optical imaging platform by integrating heavy water (D 2 O) probing with stimulated Raman scattering (DO‐SRS) microscopy, for the first time, to directly visualize and quantify lipid metabolism regulated by different diets and insulin signaling pathway in Drosophila fat body during aging. We found that calorie restriction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…Both groups showed a positive correlation between LD size and metabolic activity, suggesting that larger LDs have higher metabolic activity. This result is consistent with our studies on Drosophila fatbody metabolic activity (45-47). Importantly, quantitative analyses of CD/CH 2 ratio showed that the average lipid turnover rate in the high glucose group was about 10 times higher than that in the control group, suggesting more newly synthesized lipids were accumulated in flies on high glucose diet (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Both groups showed a positive correlation between LD size and metabolic activity, suggesting that larger LDs have higher metabolic activity. This result is consistent with our studies on Drosophila fatbody metabolic activity (45-47). Importantly, quantitative analyses of CD/CH 2 ratio showed that the average lipid turnover rate in the high glucose group was about 10 times higher than that in the control group, suggesting more newly synthesized lipids were accumulated in flies on high glucose diet (Fig.…”
Section: Resultssupporting
confidence: 94%
“…The general lipid loss in old brains was likely due to the reduction of lipid synthesis or misallocation of lipids in LDs. Our results demonstrated that the regulation of lipid storage in the brain is a highly dynamic process as that in the adipose tissue 18 , which is balanced between lipid synthesis and mobilization at LDs. The metabolic homeostasis resolved at the aging of single LDs might further determine the brain aging.…”
Section: Do-srs Imaging Reveals Reduced Metabolic Activities In Singl...mentioning
confidence: 66%
“…We first visualized de novo lipogenesis using D 2 O probing with SRS (DO-SRS) imaging. After feeding flies at different ages (0, 10, 20, 30, 40 days posteclosion) with 20% D 2 O-containing standard diets for 5 days, we imaged LDs in the brains (Figure S4A) and quantified lipids turnover rate by the ratio of CD signal (newly-synthesized lipids) to CH signal (total lipids) collected at 2143 cm -1 and 2850 cm -1 , respectively 17,18 . As shown in Figures 2B and 2C, the lipids turnover rate (CD/CH ratio) displays a bell-shaped curve in aging female and male flies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations